2015
DOI: 10.5114/pr.2015.57466
|View full text |Cite
|
Sign up to set email alerts
|

Phlebogriffe – a new device for mechanochemical ablation of incompetent saphenous veins: a pilot study

Abstract: Objectives: The aim of this study was to evaluate the feasibility, safety and early results of mechanochemical ablation of incompetent varicose veins using a special catheter: the Phlebogriffe. Material and methods:The design of this catheter is based on a typical diagnostic catheter. Into this catheter a metal shank, attached to which are 5 thin, curved, springy wires with sharpened ends, is introduced. After being pushed out of the catheter, these wires deploy into a cat's claw pattern. When the whole device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Moreover, our results are consistent with the preliminary results of other authors using this specific technique, however based on the smaller group of patients. Ciostek et al in their preliminary study, reported efficacy of the system reaching 94.9% after 3 months of follow-up [24].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, our results are consistent with the preliminary results of other authors using this specific technique, however based on the smaller group of patients. Ciostek et al in their preliminary study, reported efficacy of the system reaching 94.9% after 3 months of follow-up [24].…”
Section: Discussionmentioning
confidence: 93%
“…z o.o. seems to be an interesting proposal, extending the possibilities of effective solution of the problem of GSV/SSV insufficiency, perfectly matching the definition of the minimally invasive procedure [5,6].…”
Section: Introductionmentioning
confidence: 80%
“…The ClariVein device (Vascular Insights, LLC, Quincy, MA, USA) is at the moment the most popular MOCA system [1,2]. Recently, the Flebogrif system (Balton, Warsaw, Poland) has also become commercially available [7]. Mechanochemical ablation with the ClariVein is gaining popularity among medical professionals and patients.…”
Section: One-year Results Of Fifty Consecutive Patients Treated With mentioning
confidence: 99%